Empirical Musicology: An Interview with David Huron Part I - Shanahan, Daniel (Empirical Musicology Review, 2020)
On the occasion of David Huron's retirement, EMR Editor, Daniel Shanahan, recently interviewed him regarding the founding of the journal, the growth of empirical musicology, digital corpus studies, the Humdrum Toolkit, and related topics. The first of two interviews.